SAT0449 EFFECT OF CHOLESTEROL AND TRIGLYCERIDE ON THE FREQUENCY OF GOUT ATTACKS. (June 2019) - Lin, LI; Lu, Qun-Qun; Tao, Jinhui; Zhang, Hong-Liang; Tang, Yu-Jie; Xin-Ya, LI; Zhu, Zi-Wen
Abstract : Background: Gout is an autoinflammatory disease characterized by hyperuricemia and recurrent arthritis. ATP and MSU synergistically activate NALP3 inflammasome to induce the secretion of IL-1β, leading to the onset of gouty arthritis, and P2X7R plays a key role in gout [1, 2] . This mechanism above can explain the clinical phenomenon that some patients with hyperuricemia never suffer gouty arthritis, however, it cannot explain why the frequency of gout attacks increases as the course prolongs. Cholesterol or triglyceride can activate the innate immune and induce inflammatory response. It is speculated that Cholesterol and triglyceride levels can increase with the duration of gout, and they may reduce the threshold of gout attacks. Objectives: To demonstrate the effect of elevated cholesterol and triglyceride on the onset of gout. Methods: A cohort study was performed to observe the difference of arthritis episodes between the high cholesterol group and the normal, the high triglyceride group and the normal in gout patients. The frequency of gout attacks was compared using statistical methods of independent sample test and paired sample test between the two groups. Results: A cohort study was performed to observe the difference of arthritis episodes between the high cholesterol group and the normal, the high triglyceride group and the normal in gout patients. The frequency of gout attacks was compared using statistical methods of independent sample test and paired sample test between the two groups. RESULTS: A total of 68 patients with gout were observed. Among them, 21 were in normal cholesterol group, 13 in elevated group, 21 in normal triglyceride group and 13 in elevated group. The results of the independent sample test between the two groups are as follows: (1) The frequency of gout attacks between the normal cholesterol group and the elevated group is statistically significant within three months, six months and one year (0.81±0.60 vs 1.77±0.83, Z=-3.200, P =0.001; 1.14±0.73 vs 3.15±2.15, Z=-3.430, P =0.001; 1.43±0.81 vs 4.77±3.44, Z=-3.199, P =0.001). (2) The frequency of gout attacks between the normal triglyceride group and the elevated group is statistically significant within three months, six months and one year (0.81±0.60 vs 1.54±0.97, Z=-2.359, P =0.018; 1.14±0.73 vs 2.38±1.66, Z=-2.417, P =0.016; 1.43±0.81 vs 3.54±2.50, Z=-3.005, P =0.003). The results of the paired sample test between the two groups are as follows: (1) 6 pairs of normal cholesterol group and elevated group were screened according to age, course and uric acid level. There is significant difference in the frequency of gout attacks between the two groups within six months and one year (1.17±0.75 vs 2.83±2.23, Z=-2.060, P =0.039; 1.33±0.82 vs 4.17±3.43, Z=-2.032, P =0.042). (2) 11 pairs of normal triglyceride group and elevated group were screened as above. There is significant difference in the frequency of gout attacks between the two groups within one year (1.45±0.82 vs 3.45±2.58; Z=-2.328, P =0.020). Conclusion: Cholesterol and triglyceride levels can affect the frequency of gout attacks. The phenomenon mentioned in background can be explained by the increase of cholesterol and triglyceride levels as the course prolongs. Acknowledgement: This work was supported by grants from the National Natural Science Foundation of China (81771774) and the Anhui Provincial Natural Science Foundation (1708085MH191) References: [1] Tao JH, et al. P2X7R: A potential key regulator of acute gouty arthritis. Semin Arthritis Rheum. 2013; 43(3): 376-380. [2] Tao JH, et al. Single nucleotide polymorphisms associated with P2X7R function regulate the onset of gouty arthritis. PLoS One. 2017Aug10;12(8):e0181685. Disclosure of Interests: None declared